The Effect of Price Increases on Fresh Meat Consumption in Turkey - Bekir Demirtas (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2018)
The rapid increase of the red meat price in Turkey in the recent years negatively affects its consumption. Consumers are seeking to compensate for the need for animal protein with cheaper substitution products. In this study, the effects of consumer attitudes, product prices and some other variables on the factors affecting consumption of fresh red meat are examined. A 58‑item questionnaire measuring Behavior and Behavioral Intention was applied to 455 consumers in the Eastern Mediterranean Region of Turkey based on the Theory of Planned Behavior. In the study, participants’ consumption of fresh red meat and white meat was examined together. In the analysis of the data, correlation, independent samples’ t‑test and One Way Anova was used together with Path Analysis which is a Structural Equation Model technique. Price increases have a negative impact on fresh meat consumption and the effect on consumption of red meat is much higher. The Structural Model explains 80 % of the Behavioral Intention variance and 87 % of the Behavioral variance. In consumers’ Behavior and Behavioral Intention in meat consumption Attitude, Perceived Behavioral Control and Price variable have a significant influence, while the effect of Subjective Norms on a lower level. Socioeconomic and demographic variables cause significant differences in fresh meat consumption. Reducing the increases in input prices, which is the most important source of the increase in red meat prices in Turkey, in the short and medium terms, and supporting the supply increases by sustaining its implementation in the medium and long terms should be adopted as basic policies.